Root uptake dominates mercury accumulation in permafrost plants of Qinghai-Tibet Plateau - Wang, Xun; Yuan, Wei; Lin, Che-Jen; Wang, Dingyong; Luo, Ji; Xia, Jicheng; Zhang, Wei; Wang, Feiyue; Feng, Xinbin (Communications Earth & Environment, 2022)
Uptake of atmospheric elemental mercury via foliage is thought to be the dominant pathway of mercury accumulation in terrestrial ecosystems, including those in the Arctic permafrost regions. Whether a similar process operates in alpine permafrost regions remains unknown. Here we report mercury concentrations and stable isotopic signatures in a large cluster alpine permafrost regions of mid-latitude Qinghai-Tibet Plateau. We find a transition from foliage to root uptake of mercury as elevation increases. In alpine permafrost regions, we find that root uptake of mercury from the surrounding soil is the dominant accumulation pathway. We estimate that root uptake accounts for 70 +/- 19% of plant mercury in permafrost regions of the Qinghai-Tibet Plateau and propose that this may be related to the harsh climate conditions suppressing foliage growth and promoting lateral root growth. Mercury accumulation in alpine permafrost vegetation via root uptake increases with altitude relative to foliage uptake from the atmosphere, according to analyses of mercury concentrations and isotopic signatures in grass and soil profiles in the Qinghai-Tibet Plateau.